Serbo-Croat Clitics and Word Grammar - Čamdžić, Amela; Hudson, Richard (Research in Language, 2007)
Serbo-Croat has a complex system of clitics which raise interesting problems for any theory of the interface between syntax and morphology. After summarising the data we review previous analyses (mostly within the generative tradition), all of which are unsatisfactory in various ways. We then explain how Word Grammar handles clitics: as words whose form is an affix rather than the usual ‘word-form’. Like other affixes, clitics need a word to accommodate them, but in the case of clitics this is a special kind of word called a ‘hostword’. We present a detailed analysis of Serbo-Croat clitics within this theory, introducing a new distinction between two cases: where the clitics are attached to the verb or auxiliary, and where they are attached to some dependent of the verb.